Neoadjuvant Immunotherapy as a risk factor for Hashimoto’s Disease - Araujo-Filho, Irami; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
This review investigates the association between neoadjuvant immunotherapy and the onset of Hashimoto's disease in patients with neoplastic conditions. With the increasing use of immunotherapy in oncology, understanding potential immune-related adverse events, particularly autoimmune thyroiditis, is crucial for optimizing patient outcomes and managing therapy-related risks. Our findings suggest a notable incidence of Hashimoto's disease among cancer patients receiving neoadjuvant immunotherapy. The underlying mechanisms may involve immune checkpoint inhibitors disrupting immune tolerance, leading to autoimmune thyroiditis. This review highlights the need for vigilant monitoring of thyroid function in patients undergoing immunotherapy and suggests potential strategies for early detection and management of Hashimoto's disease in this population. Further research is required to elucidate the precise mechanisms and risk factors involved, which could inform clinical guidelines and improve patient care.